Strength and durability of concrete with bentonite clay and quarry dust - Umar, Muhammad; Qian, Hui; Khan, M. Nasir Ayaz; Siddique, Muhammad Shahid; Almujibah, Hamad; A. Elshekh, Ali. E.; Bashir, Maaz Osman; Vatin, Nikolai Ivanovich (Frontiers in Materials, 2025)
The research object is concrete with supplementary cementitious materials (SCMs) such as bentonite clay and quarry dust. The impact of incorporating these SCMs on fresh concrete properties, compressive, flexural, and split tensile strengths, and acid resistance was investigated. Microstructural analysis using Scanning Electron Microscopy (SEM) and X-ray radiography were used. Varying proportions of SCMs (5%–20%) were incorporated into the concrete mix while maintaining a constant water-to-cement ratio. Key findings reveal a 7.31% increase in compressive strength, a significant 19.7% improvement in flexural strength, and enhanced acid resistance. Utilizing Response Surface Methodology (RSM), the optimal mix design for achieving superior mechanical strength was identified. The quadratic model of RSM indicated that a combination of 10.29% bentonite clay, 7.20% quarry dust, and 8.19% fine aggregate replacement yielded the highest strength. Predictive and experimental results demonstrated strong agreement. Compared to the reference concrete, the optimized samples exhibited significant increases of 18.08%, 33.60%, and 11.15% in compressive, flexural, and tensile strengths, respectively. This research demonstrates the potential of locally available SCMs as viable and sustainable alternatives for concrete production, offering improved performance without compromising strength.